PERTUNJUKAN TARI: SEBUAH KAJIAN PERSPEKTIF GENDER - Titik Putraningsih (Imaji, 2006)
Up to now, there is still a little number of activities for female choreographers sothat we can rarely watch dance performances composed by them. However,some dance performances in Yogyakarta and Surakarta are composed by femalechoreographers with gender themes. Setyastuti, Inong and Maruti perform theirworks with various themes related to woman life in Indonesia and describe theroles of women in the colonial era through these works. Some of the works areinteresting to be discussed from the gender perspective. The term ‘gender’ refersto social, cultural, and biological senses. This perspective leads to a view orunderstanding about women’s roles that are determined by nature, and theirgender roles, which are determined by society and culture. The different genderfor men and women creates problems if it causes unfair treatment related to menand women’s rights and opportunities.Keywords: dance performance, gender, female choreographers